Inheritance of pseudostem waxiness in banana and plantain (Musa spp.) - Ortíz, R.; Vuylsteke, D.R.; Ogburia, N.M. (1995)
Bananas and plantains (Musa spp. L.) are important staple food crops in tropical countries. A major constraint to their sustainable production is black sigatoka leaf spot disease, caused by the fungus Mycosphaerella fijiensis Morelet. Resistance breeding is the most appropriate intervention to control this disease. Presence of epicuticular wax in leaves is one trait that may be involved in host plant resistance to the fungus. The inheritance of waxiness in the pseudostem, which is composed of overlapping leaf sheaths, was studied. Segregating populations were obtained by crossing triploid cultivated Musa and diploid improved bananas with diploid cultivated and wild bananas. Tetraploid, triploid, and diploid individuals were recovered from the triploid x diploid crosses, in which one of the diploids was the wild banana Calcutta 4. Calcutta 4 bred true for pseudostem waxiness. A diploid F1 hybrid was then selfed to produce an F2. The F2 population segregated into 29 individuals with a nonwaxy pseudostem and 6 with a waxy pseudostem, suggesting that pseudostem waxiness is due to a recessive allele, wx. Results from other crosses between Calcutta 4 and other recessive waxy parents, however, indicated that alleles with mainly additive effects are responsible for modifying the action of the dominant allele Wx. Moreover, a clear dosage effect, i.e., an increase in the expression of the trait in tetraploids, was observed. The midparent regression values were 0.67